"Aging in Place" - Prädiktoren für den Wunsch nach Betreutem Wohnen zu Hause - Beyer, Anja; Treml, Manuela; Rupprecht, Roland (Deutsche Gesellschaft für Gerontologie und Geriatrie Jahrestagung Sektion III und IV, 2017)

Befragung der Bevölkerung 50+ der Marktgemeinde Wendelstein über Wünsche, Bedürfnisse und konkrete Planungen für das eigene Alter : Abschlussbericht - Rupprecht, Roland; Beyer, Anja; Lang, Frieder (2012)

Dementia Worry and the Perception of Personal Risk: A Longitudinal Study - Martin, Kristina; Lang, Frieder; Rupprecht, Roland; Nömer, Jessica (GeroPsych, 2020)
The research examined dementia worry and the perception of personal dementia risk based on a 2-year longitudinal online study (N = 129, 21-79 yrs). Participants completed questionnaires on attitudes, experiences, and worries concerning dementia. A fully saturated cross-lagged model was estimated. Results show that dementia worry was moderately stable, and that changes were unrelated to perceived risk or family history. In contrast, perceived dementia risk was more prone to change and was positively associated with prior dementia worry but not vice versa. Having a family history of dementia was cross-sectionally, but not longitudinally, associated with greater worry and higher perceived risk. Because of the limited variability of dementia worry, focusing on perception of personal risk is a promising approach. Future research may benefit from differentiating the plasticity of the two constructs.
CRIS-Team Scopus Importer:2020-10-30
Keywords: dementia worry; family history of dementia; risk perception; stability

Differential effects of single versus combined cognitive and physical training with older adults: The SimA study in a 5-year perspective - Oswald, Wolf Dieter; Gunzelmann, Thomas; Rupprecht, Roland; Hagen, Bernd (European Journal of Ageing, 2006)
The present study evaluates the effect of cognitive training, of psychoeducational training and of physical training on cognitive functioning, physical functioning, physical health, independent living and well-being in older people. Also the combination of physical training with cognitive training or psychoeducational training, respectively, was evaluated. In contrast to most training studies with older people, training effects were evaluated in a longitudinal perspective over 5 years to analyse long-term-results of cognitive and physical activity on older adults. Training effects were evaluated compared to a no-treatment-control group. Subjects were 375 community residents aged 75-93 years. Up to 5 years after baseline examination, significant training effects were observed in the group exposed to the combined cognitive and physical training. The physical and cognitive status in the participants of this group could be preserved on a higher level compared to baseline, and the participants displayed fewer depressive symptoms than the no-treatment-control group. The results are discussed in the light of recent research regarding the effects of mental and physical activity on brain function in older adults. © Springer-Verlag 2006.
Keywords: Cognitive training; Physical training; Independent living; Dementia

Dizziness in an older community dwelling population: A multifactorial syndrome - Gaßmann, Karl-Günter; Rupprecht, Roland (Journal of Nutrition, Health & Aging, 2009)
Objectives: The aim of this study was to determine the prevalence and related predictors of dizziness in a sample of community-dwelling people 65 years of age and older living in a metropolitan area in Germany. Design: Prospective cohort study. Setting: Interdisciplinary Centre of Gerontology at the University of Erlangen-Nuremberg, Germany. Participants: 6000 people aged 65 years and older recruited and randomized from the registration office, 1801 were fully evaluated at baseline and were re-evaluated in a prospective follow-up two years later. A full data set was obtained for 620 participants, of which 297 (47.9%) were females. Mean age was 73.45 ± 6.05. 200 participants (32.4%) were 65-69 years, 315 (51%) were 70-79 years, 92 (14.9%) 80-89 years and 11 (1.8%) 90 years and older. Measurements: Demographic, medical, functional and psychological factors were measured by a standardised questionnaire in 2004. In a follow-up survey participants were reevaluated in a prospective design two years later (2006), including a dizziness questionnaire, containing frequency, duration, space of dizziness and releasing positions and activities. Results: At the second measurement 181 persons (29.2%) reported dizziness in the last 6 months. Dizziness was age dependent, with a prevalence of 27% in participants aged 70 years and younger, up to 54% in the group of 90 years and older. 96 (68.2%) persons reported daily or weekly dizziness. 46 (27.9%) participants reported multiple sensations of dizziness. In 108 (59.7) persons dizziness was released by multiple positions or activities. The main predictors of dizziness were age, female gender, cardiovascular disease, osteoporosis, depression, sleep disorder, disturbance of memory, shortsightedness (defined by glasses), incontinence, 3 and more medical conditions, 4 and more medications, poor health status, falls and mobility problems. We found similar risk factors for dizziness and falls. Conclusion: Dizziness is a very common symptom in older community dwelling persons. Comorbidity, poor health status and mobility problems are strong medical predictors; age and female gender and decline in mobility are important predictors as well. Our study suggests, that dizziness in older age is often caused by multifactorial medical and functional conditions. Gait disorders and mobility problems also seem to play an important role in dizziness among older people. Therefore, interventions in dizziness should be developed in a multifactorial way. We suggest, that the interventions to be tested first, should be those that have been previously successful in older persons with gait disorders and falls.

Dizziness in an older community dwelling population: Multifactorial syndrome - Gaßmann, Karl-Günter; Rupprecht, Roland (Journal of Nutrition, Health & Aging, 2009)
Keywords: Old age; Risk factor; Gait disorders; Dizziness

Gerontopsychologische Diagnostik - Rupprecht, Roland; Gunzelmann, Thomas; Oswald, Wolf Dieter (Alterspsychotherapie und klinische Gerontopsychologie. 2. Aufl., 2014)
Keywords: Diagnostik; Gerontologie

Interventionsrelevante Konzepte der lebenslangen Entwicklung - Lang, Frieder; Rupprecht, Roland (Angewandte Gerontologie : Interventionen für ein gutes Altern in 100 Schlüsselbegriffen, 2012)

Kognitive Beeinträchtigungen und Depressivität im Alter: Effekte subjektiver Symptome im Vergleich zu psychometrischen Befunden und klinischer Einschätzung - Rupprecht, Roland; Lang, Frieder (Zeitschrift für Gesundheitspsychologie, 2013)
Cognitive impairment in old age is often related to increased psychological stress and depressive symptoms. We explored to what extent effects of cognitive impairment in old age may be buffered with educational resources. In our study, 201 older adults visited a diagnostic counseling service at a gerontological research institute and reported subjective cognitive complaints. Three groups of participants were identified: patients with moderate dementia symptoms (n=77), mildly cognitively impaired patients (n=78), and healthy persons with only subjective cognitive impairment (n=46). We compared associations of self-reported complaints with depressive symptoms between the groups controlling for resources and health status. Results showed that self-reported complaints were positively associated with depressive symptoms independent of cognitive performance, education, and family status. However, educational resources moderated this association: More highly educated individuals responded with fewer depressive symptoms to experiencing subjective cognitive loss. Our findings suggests that higher education may serve as a compensatory resource in coping with age-related cognitive loss. © Hogrefe Verlag, Göttingen 2013.
Keywords: cognitive impairment; depression

Personelle Ausstattung und Versorgungsqualität in bayerischen Alten- und Pflegeheimen : Bestandsaufnahme, Literaturüberblick und Feldstudie zu den Auswirkungen unterschiedlicher Leitungsmodelle auf die Versorgungsqualität - Lang, Frieder; Rupprecht, Roland; Engel, Sabine; Beyer, Anja; Kraus, Bertram; Liebich, Corinna; Volland-Schüssel, Käte; Sonnenberg, Magdalene (2009)

POSITIVE ASSOCIATION OF PRO-INFLAMMATORY PROCESSES WITH PSYCHOSOCIAL WELL-BEING IN HIGHLY FUNCTIONAL NONAGENARIANS - Rohleder, Nicolas; Rupprecht, Roland; Lang, Frieder (PSYCHOSOMATIC MEDICINE, 2019)
CRIS-Team WoS Importer:2019-05-28

Prediction of future falls in a community dwelling older adult population using instrumented balance and gait analysis - Bauer, Christoph; Gröger, Ines; Rupprecht, Roland; Marcar, V.L.; Gaßmann, Karl-Günter (Zeitschrift für Gerontologie und Geriatrie, 2015)
Background: The role of instrumented balance and gait assessment when screening for prospective fallers is currently a topic of controversial discussion. Objectives: This study analyzed the association between variables derived from static posturography, instrumented gait analysis and clinical assessments with the occurrence of prospective falls in a sample of community dwelling older people. Methods: In this study 84 older people were analyzed. Based on a prospective occurrence of falls, participants were categorized into fallers and non-fallers. Variables derived from clinical assessments, static posturography and instrumented gait analysis were evaluated with respect to the association with the occurrence of prospective falls using a forward stepwise, binary, logistic regression procedure. Results: Fallers displayed a significantly shorter single support time during walking while counting backwards, increased mediolateral to anteroposterior sway amplitude ratio, increased fast mediolateral oscillations and a larger coefficient (Coeff) of sway direction during various static posturography tests. Previous falls were insignificantly associated with the occurrence of prospective falls. Conclusion: Variables derived from posturography and instrumented gait analysis showed significant associations with the occurrence of prospective falls in a sample of community dwelling older adults.
Keywords: Accidental falls; Gait; Geriatric assessment; Postural balance; Prognosis

Predictors for occasional and recurrent falls in community-dwelling older people - Gaßmann, Karl-Günter; Rupprecht, Roland; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2009)

Psychologische Theorien zum Alternsprozess - Rupprecht, Roland (Gerontopsychologie (2. akt. u. erw. Aufl.), 2008)

Reliability analysis of time series force plate data of community dwelling older adults - Bauer, Christoph; Gröger, Ines; Rupprecht, Roland; Meichtry, Andre; Tibesku, C.O.; Gaßmann, Karl-Günter (Archives of gerontology and geriatrics, 2010)
Frequency-based analysis of body sway has been used to distinguish between healthy young, healthyelderly adults and elderly adults with Huntingtons disease. Our aim was to assess the reliability of spectral-based outcomes of the centre of pressure (CoP) kinematics in order to determine if these outcomes could be tested for their capability to distinguish between elderly fallers and non-fallers in a future study. We have studied balance for 30 community dwelling healthy older adults 60 years or older. Four test conditions were used. Three successive trials were performed for each condition. CoP kinematics were estimated with a force platform with three strain gauges set in a triangular position. The frequency content of these signals was estimated. Intrasession correlation coefficients (ICC’s) were then calculated for all test conditions. The reliability of the selected parameters varied between low and high (ICC 0.652–0.939). The ICC’s for the narrow stance tests were higher compared to tests with normal standing conditions (0.771–0.94) to (0.652–0.865). The highest value was obtained in the high frequency band (0.939). These measures should be viewed with caution when screening geriatric patients because their reliability cannot always be assumed.
Keywords: Falls in elderly; Reliability; Posture; Balance

Subjektive Restlebenszeit und vorsorgende Umzugsplanung in der zweiten Lebenshälfte - Beyer, Anja; Rupprecht, Roland; Lang, Frieder (Zeitschrift für Gerontologie und Geriatrie, 2016)
Hintergrund. Obwohl viele Menschen möglichst lange in der gewohnten Wohnumgebung verbleiben wollen, setzen sie sich dennoch mit der eigenen Wohnzukunft auseinander. Denn Wohnen im Alter steht im Spannungsfeld zwischen Kontinuität und Reagieren auf altersbedingte Veränderungen. In diesem Zusammenhang ist der Einfluss der subjektiven Restlebenszeit auf die Zukunftsplanung, etwa bezogen auf die eigene Wohnsituation, wenig erforscht. Ziel der Arbeit. Dieser Beitrag geht der Frage nach, welchen Einfluss die Wahrnehmung des eigenen Zeithorizonts auf die Planung eines möglichen Umzugs und dessen zeitliche Einordnung im Lebensverlauf hat. Material und Methoden. Daten aus einer postalischen Befragung von 2156 Personen ab 50 Jahren zu ihren Wünschen und Planungen für das eigene Alter konnten ausgewertet werden. Hierbei wurden auch die Umzugsplanung und die subjektive Restlebenszeit erfasst. Die Teilnehmer waren durchschnittlich 65,5 Jahre alt (SD ± 9,7 Jahre, Range 50 bis 94 Jahre); es waren 51,1 % der Teilnehmer weiblich. Ergebnisse. Etwa 39 % der Befragten erwägen im weiteren Lebensverlauf einen Umzug. Es zeigte sich, dass neben Soziodemografie, Wohnsituation und Gesundheit auch die subjektive Restlebenszeit Einfluss auf die Umzugsplanung im Alter und deren zeitliche Einordnung im weiteren Lebensverlauf hat. Personen, die eine geringe Restlebenszeit angeben, erwägen einen Umzug in einem höheren Alter (abwartende Planung) als Personen, die mehr Restlebenszeit verspüren. Deren zeitliche Einordnung einer eher vorsorgenden Umzugsplanung ist in jüngeren Jahren verankert. Schlussfolgerungen. Gedanken zur eigenen Wohnzukunft im Alter sollten nicht nur nach den Inhalten, sondern auch im Zusammenhang mit dem eigenen Zeithorizont und der Einordnung in den individuellen Lebensverlauf betrachtet werden. Dies kann Beratungsund Entscheidungssituationen unterstützen.
Keywords: Wohnzukunft; Zukunftsorientierung; Restlebenszeit; Umzugsplanung; Ältere; 50 Jahre und älter

Subjektive Restlebenszeit und vorsorgende Umzugsplanung in der zweiten Lebenshälfte - Vergleich von urbanem und ländlichem Raum - Beyer, Anja; Rupprecht, Roland; Lang, Frieder (5. gemeinsamer Kongress der Deutschen Gesellschaft für Gerontologie und Geriatrie (DGGG) und der Schweizerischen Gesellschaft für Gerontologie (SGG), 2016)

The Erlangen instrument of alternating word fluency in dementia (EAWF-D): A new assessment tool combining set-shifting and semantic word fluency - Engel, Sabine; Rupprecht, Roland; Mahlberg, Richard (GeroPsych, 2011)
The Erlangen Instrument of Alternating Word Fluency in Dementia (EAWF-D) is a new alternating word fluency task that combines set-shifting and semantic word fluency based on psycholinguistic theory that the ability to switch between two different semantic categories should already be impaired in beginning dementia. N = 138 (58.7% female; age: M = 73.9; SD = 7.03) outpatients of a memory clinic were diagnosed according to the ICD-10 criteria: subjective memory complainers (N = 60), mild cognitive impairment (N = 37), and mild to moderate dementia (N = 41). An analysis of variance of the EAWF-D revealed a significant main effect of diagnosis (F(2, 135) = 46.7; p < .001; η = .41). The EAWF-D score correlates significantly with the MMSE total score (r = .54, p < .001) as well as with MMSE subscores "Orientation" (r = .41, p < .001) and "Recall" (r = .53, p < .001). Ordinal logistic regression analysis confirmed the potential for diagnosis of beginning dementia. © 2011 by Hogrefe Publishing.
Keywords: alternating word fluency; set-shifting; mild cognitive impairment; dementia

The frailty syndrome in general practitioner care - A pilot study - Drey, Michael; Wehr, H.; Wehr, Gritt; Uter, Wolfgang; Lang, Frieder; Rupprecht, Roland; Sieber, Cornel; Bauer, Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2011)
Background: Knowledge about frailty among patients seen by general practitioners (GP) is currently limited. Patients and methods: Frailty assessment by the criteria of Fried and additional documentation was performed at a GP’s office. Results: Out of 119 participating patients, 14.3% were classified as frail, 52.1% as prefrail, and 33.6% as not frail. Frailty was associated with comorbidity, the number of drugs prescribed, depressive symptoms, cognitive function, and frequency of falls. Conclusion: The prevalence of frailty is high among the cohort of elderly persons seen by a GP. Routine frailty assessment will help to direct preventive and therapeutic interventions.
Keywords: Frailty; Fried criteria; General practitioners; Elderly; Prevalence

The Impact of Perceived Knowledge of Dementia on Caregiver Burden - Schindler, Manuel; Engel, Sabine; Rupprecht, Roland (GeroPsych, 2012)
This study centered around 131 caregivers and their recipients to investigate whether the caregiver’s perceived knowledge of dementia may be a factor in reducing caregiver burden. We developed a questionnaire to measure this kind of knowledge. A significant relationship was shown between perceived knowledge and caregiver burden. Our multivariate analysis furthermore demonstrated that the caregivers’ self-assessed state of health also has a significant influence. A second regression model included the different aspects of perceived knowledge of our questionnaire and showed that certain aspects of perceived knowledge, especially concerning existing professional help services, noncognitive symptoms of dementia, and the importance of not neglecting one’s own personal needs, has an positive impact on caregiver burden.
Keywords: perceived knowledge; caregiver burden; dementia

Therapie mit Demenzkranken in einer geriatrischen Tagesklinik: Verbesserung von Verhaltensauffälligkeiten und Belastungserleben der Angehörigen - Wunner, Christina; Rupprecht, Roland; Singler, Katrin; Söllner, Wolfgang; Waller, Christiane; Gosch, Markus; Schubert, Anne (Zeitschrift für Gerontologie und Geriatrie, 2020)
Background and objective: The aim of the study was to evaluate a specific treatment concept for patients suffering from dementia in a geriatric day clinic with respect to improvement of dementia-related behavioral abnormalities and effects on distress of the caring relatives. Material and methods: Designed as a naturalistic study with a sample of 34 dementia patients (average age 83 years, 62% female, 82% mild dementia, 18% moderate dementia) surveyed at three time points, the dementia-related behavioral symptoms and the relatives’ distress were measured using the neuropsychiatric inventory. A waiting time before treatment was implemented as a control condition. Results: Compared with waiting time, a significant improvement of dementia-related behavioral abnormalities was found after treatment, especially in patients suffering from moderate dementia. The distress of caring relatives was clearly reduced. Conclusion: The interprofessional treatment of patients with dementia using a specific program in a geriatric day clinic leads to a clear improvement in behavioral symptoms and positively influences the distress of caring relatives.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Caring relatives; Distress; Geriatric day hospital; Problem behavior; Treatment outcome

What do cognitive complaints in a sample of memory clinic outpatients reflect? - Mascherek, Anna; Zimprich, Daniel; Rupprecht, Roland; Lang, Frieder (GeroPsych, 2011)
Conflicting evidence exists concerning the value of cognitive complaints in the course of assessing cognitive performance in individuals. The present study examines whether cognitive complaints are differentially related to cognitive functioning in groups with different diagnoses. 169 older outpatients (76 years on average) were divided into three groups and diagnosed with subjective cognitive complaints, mild cognitive impairment, or dementia. They were then administered a self-rating questionnaire on cognitive complaints, with semantic fluency and global cognitive functioning being assessed as cognitive measures. Multiple regression analyses revealed that, after controlling for depression, age, sex, and education, global cognitive functioning was not related to cognitive complaints. Semantic fluency was related to cognitive complaints depending on the group. Results suggest that cognitive complaints reflect, in part, actual cognitive performance. © 2011 by Hogrefe Publishing.